(untitled) (Eurasian Scientific Herald, 2022)
The article reveals the importance of the formation of sociolinguistic competencies of future teachers in the process of socialization and professional adaptation. Structural elements of sociolinguistic competencies are also analyzed from pedagogical and linguistic points of view.